PENGARUH WATER COOLANT TERHADAP EFEKTIFITAS RADIATOR PADA MESIN TOYOTA KIJANG SERI 4K - Elfiano, Eddy; Suripto, Heri; Hastuti, Kurnia; Rahman, Jhonni; Subekti , Purwo; Zinomeza , Eho (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The cooling system of an engine utilizes a radiator to regulate the temperature of the coolant, whice absorbs heat from engine to maintain its optimal operating temperature. The aim of the research is to evaluate the effectiveness of radiator using defferent types of water coolants, including gallon water. The study involves using a Toyota Kijang 4K series engine mounted on an engine stand. Data collection includes conducting four rotational variations for each coolant, incluidng galon water. The collected data includes parameters such as inlet and outlet temperature of the coolant, air temperature in front of and behind the radioator, wind speed measurements in those areas, and observation of the coolant flow rate. The findings reveal that coolant C demonstrates the highest average effevctiveness among the different coolant, with a value of 25,28%. Coolant B shows an average effectiveness of 21,98%, while coolant A has an average effectiveness of 21,30%. Galon water exhibts the lowest average effevtiveness, with a value of 18.33%. the radiator’s effectiveness is directly related to the rate of heat transfer, meaning that a higher heat transfer rate corresponds to a higher radiator effectiveness. Thus, based on this study, it can be concluded that coolant C is the most effective coolant in terms of radiator efectiveness and heat transfer.